2017
DOI: 10.1590/s0100-204x2017001000016
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of elephant grass genotypes

Abstract: -The objective of this work was to assess the nutritive value of four elephant grass (Pennisetum purpureum) genotypes. The chemical composition, intake by sheep, and digestibility of different genotypes (G1, G2, G3, and G4) were evaluated. A dry matter (DM) digestibility assay was performed with total leftovers and feces collected from 20 sheep kept in metabolic cages. G3 had lower DM intake in grams per animal per day compared with G1 and G2, and it had greater digestibility, crude protein, neutral detergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Moreover, the proportion of morphological components in tall-sized genotypes is different in comparison to that of short-sized grasses. In general, there are more dead or senescent materials and a lower percentage of leaf blades (QUEIROZ et al, 2000;GOMIDE et al, 2015;SOUZA et al, 2017), which can be explained by the great proportion of basilar tillers of these genotypes, because basal tillers tend to present higher senescence rate compared to aerial tillers (PACIULLO et al, 2003). SOUZA et al (2017) observed a leaf blade (lB) proportion of 29.50% and a dead material (DDM) proportion of 29.67% in the tall-sized genotype 'CNPGl 96-27-3'.…”
Section: Tall-sized Elephant Grassmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the proportion of morphological components in tall-sized genotypes is different in comparison to that of short-sized grasses. In general, there are more dead or senescent materials and a lower percentage of leaf blades (QUEIROZ et al, 2000;GOMIDE et al, 2015;SOUZA et al, 2017), which can be explained by the great proportion of basilar tillers of these genotypes, because basal tillers tend to present higher senescence rate compared to aerial tillers (PACIULLO et al, 2003). SOUZA et al (2017) observed a leaf blade (lB) proportion of 29.50% and a dead material (DDM) proportion of 29.67% in the tall-sized genotype 'CNPGl 96-27-3'.…”
Section: Tall-sized Elephant Grassmentioning
confidence: 99%
“…In general, there are more dead or senescent materials and a lower percentage of leaf blades (QUEIROZ et al, 2000;GOMIDE et al, 2015;SOUZA et al, 2017), which can be explained by the great proportion of basilar tillers of these genotypes, because basal tillers tend to present higher senescence rate compared to aerial tillers (PACIULLO et al, 2003). SOUZA et al (2017) observed a leaf blade (lB) proportion of 29.50% and a dead material (DDM) proportion of 29.67% in the tall-sized genotype 'CNPGl 96-27-3'. Conversely, for the short-sized genotype 'CNPGl 96-24-1', the proportion was 45.80% for lB and only 0.60% for DDM.…”
Section: Tall-sized Elephant Grassmentioning
confidence: 99%
See 1 more Smart Citation
“…Kandungan nutrien rumput gajah pada penelitian ini sebanding dengan penelitian-penelitian sebelumnya. de Souza et al (2017)…”
Section: Hasil Dan Pembahasan Kandungan Nutrien Bahan Pakanunclassified
“…The high fiber content of the grasses will be degraded and fermented by rumen microbes in the rumen of goat [2]. Elephant grass contains 13% crude protein (CP) with about 60% digestibility [3]; [4]; [5]; [6].Mini elephant grass contains CP around 12% [7]; [8], whereas Panicum maximum contains 6% CP [9]; [10] ), and Brachiaria decumbens contains 9% CP with about 70% digestibility [11]; [12]. Concentration of ADF of those Elephant grass, Mini elephant grass, Panicum maximum, and Brachiaria decumbens were 38%, 34%, 40% and 44%, respectively.…”
Section: Introductionmentioning
confidence: 99%